2013
DOI: 10.12968/jowc.2013.22.10.534
|View full text |Cite
|
Sign up to set email alerts
|

Nurse–patient consultations in primary care: do patients disclose their concerns?

Abstract: If these data are representative, this has profound implications for person-centred care and shared decision-making models of care, which are predicated on patients articulating their needs. They also have implications for the development of practitioners' communication and consulting skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 21 publications
0
26
0
Order By: Relevance
“…Data from these observations was analysed descriptively 2 and revealed that 38% of patient concerns were not raised, a further 38%…”
Section: Effects On Daily Lifementioning
confidence: 99%
See 4 more Smart Citations
“…Data from these observations was analysed descriptively 2 and revealed that 38% of patient concerns were not raised, a further 38%…”
Section: Effects On Daily Lifementioning
confidence: 99%
“…2 These phases constituted preparatory work for the development of this consultation template and full details have formed the basis of earlier publications. 1,2…”
Section: Effects On Daily Lifementioning
confidence: 99%
See 3 more Smart Citations